Temporal-Spatial Characteristics of Ground and Pile Responses to Twin Shield Tunneling in Clays. (7th July 2021) - Sheng, Minghong; Gao, Jinjin; Guo, Panpan; Cao, Rihong; Wang, Yixian
Abstract : This paper investigates the temporal-spatial characteristics of ground displacements as well as vertical and horizontal displacements and axial forces in existing piles induced by twin shield tunneling in clays. To that end, a case study and three-dimensional (3D) finite element (FE) analysis were performed. Based on the in situ monitoring data from the presented twin tunneling case history with existing piles beneath, the adopted 3D FE method was validated to be competent to yield reasonable simulation results. The validated 3D FE method was then used to analyze the effects of the distance between the tunnel and the pile, the distance between tunnel faces, and the pile length on the horizontal and vertical displacements and axial stresses in piles. It was found that the horizontal displacement distribution forms along the pile shaft for the front piles are similar to that for the back piles, whereas the magnitudes of the horizontal displacements of the front piles are slightly larger than that of the back piles. The interactions between piles in the pile group provide protection of the middle piles in the pile group against twin tunneling effects. With a reduction in the distance between the tunnel and the pile, the pile displacements and stresses increase nonlinearly. With an increase in the distance between tunnel faces, the maximum positive pile displacements and the maximum and minimum axial pile stresses increase, while the maximum negative pile displacements and the difference between the maximum and minimum axial pile stresses decrease.